Exploring the social interaction among Tinder users on sexual courting - Tio, Christopher Zhee Kang; H'ng, Shu Jie; Leow, Chee Yao; Low, Min Yun; Tiew, Wan Chin (2019)
In the era of information, modernisation of technology has contributed to a contemporary way of social interaction among the society (McFarlane, 2010). Tinder is one of the online interaction platforms has provided an alternative and effective way for social interaction among the society members. Tinder has a minimum of 10 million active users. It is identified as a widely used mobile dating application that enable the users to date online through its features as compared to traditional face-to-face dating (Tanner & Tabo, 2018). In this research, researchers aim to explore the social interaction among the Tinder users on sexual courting. Since this is an exploratory research, therefore a qualitative research paradigm is used in this research. Qualitative research allows holistic apprehensions on different nature of perspectives as well as human experiences. Researchers obtained detailed data by using purposive sampling through an in-depth interview. Ten Tinder users range 18 to 35 years been selected to (iv) be interviewed. Researchers stop 10 Tinder users as it reached the saturation point. Saturation point is defined as the point which extra data could not develop new themes for the research (Saunders, Sim, Kingstone, Baker, Waterfield, Bartlam, Burroughs & Jinks, 2017). Based on the findings, majority of the users were found to be involved in sexual courting on Tinder. There are differences between male and female Tinder users. As for male users, they found Tinder through media whereas female users more likely inclined to word of mouth by using Tinder. In term of social interaction style, male Tinder users are more likely to seek for relationships as well as sexual relationship through sexual courting. However, female users tend to be reserved involving in sexual courting in a way to seek for sexual relationship on Tinder. The findings of the research can be served as a guideline for the society members, especially for young adults to prevent them from falling into sexual trap. In addition, this research can be a reference for future researchers who are interested in conducting a similar study related to social interaction involving online social interaction site. As for conclusion, throughout this research, researchers conclude that, Tinder application served as a free chat application which avenue towards free sex cultures.